2019
DOI: 10.1002/smll.201805432
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanoporous Copper Architectures via 3D Printing Technique for Highly Efficient Catalysts

Abstract: Nanoporous metals represent a class of functional materials with unique bicontinuous open porous structural properties, making them ideal candidates for various catalyst applications. However, the pursuit of nanoporous properties, extremely small pores, and high surface area, results in the restriction of mass transport. Herein, a free‐standing hierarchical nanoporous Cu material, prepared by a selective laser melting 3D printing technique and a one‐step dealloying process, is presented as a highly efficient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…On the other hand, the bicontinuous nanoscale ligament-pore structure will facilitate mass transport (both electrolyte and gas) and provide a conductive network for fast electron transfer and electrochemical reactions. [44][45][46] For possible overall water splitting in acidic media, a high HER activity is also required. As shown in Figure 5a, the HER performances of these multinary alloy catalysts follow the trend that AlNiCoIrMo&Pt/C > AlNiIr > AlNiCoIrNb&AlNiCoIr > AlNiCoIrV/AlNiCoIrCr/AlNiCoIrCu.…”
Section: Doi: 101002/smll201904180mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the bicontinuous nanoscale ligament-pore structure will facilitate mass transport (both electrolyte and gas) and provide a conductive network for fast electron transfer and electrochemical reactions. [44][45][46] For possible overall water splitting in acidic media, a high HER activity is also required. As shown in Figure 5a, the HER performances of these multinary alloy catalysts follow the trend that AlNiCoIrMo&Pt/C > AlNiIr > AlNiCoIrNb&AlNiCoIr > AlNiCoIrV/AlNiCoIrCr/AlNiCoIrCu.…”
Section: Doi: 101002/smll201904180mentioning
confidence: 99%
“…The calculated energy barriers for both the OER and HER processes are shown in Figure S6 (Supporting Information), further reflecting the high performance of the multicomponent system over pure IrO 2 . On the other hand, the bicontinuous nanoscale ligament‐pore structure will facilitate mass transport (both electrolyte and gas) and provide a conductive network for fast electron transfer and electrochemical reactions …”
mentioning
confidence: 99%
“…1: from nanometers (e.g., for dealloyed metals), to micrometers (e.g., for freeze-cast or replicated foams), to sub-millimeters (e.g., for additively manufactured lattices), to centimeters (e.g., for open-channel metals), with some porous metals displaying hierarchical macro/micro/nano pores. At the low end of this scale, with nanometer-sized pores and ligaments, are nanoporous alloys fabricated by dealloying [34][35][36] , which may be combined with methods such as additive manufacturing [37][38][39] , powder metallurgy 4,40 or other strategies to create hierarchical structure.s 41 These display promising applications in areas such as catalysis 42 , sensing 43 and energy storage. 44 The complex mechanisms underlying nanoporosity formation and coarsening [47][48][49] has also attracted great interest in fundamental mechanism studies and continuing innovation on dealloying methods such as liquid metal dealloying [50][51][52] , solid-state interfacial dealloying 53,54 , vapor phase dealloying 55,56 , and reduction/thermal decomposition 57,58 .…”
Section: Pore Size Effectsmentioning
confidence: 99%
“…More recently, Fujita et al also reported the use of an alternative AM method, selective laser melting (SLM), to make hierarchical porous Cu structures [ 87 ]. They were able to purchase commercial Cu-Mn powders for additive manufacturing.…”
Section: Dealloying and Additive Manufacturingmentioning
confidence: 99%